Gender Differences in Fat Distribution and Inflammatory Markers among Arabs - Abdulaziz Farooq; Wade L. Knez; Kelly Knez; Asma Al-Noaimi; Justin Grantham; Vidya Mohamed-Ali (Mediators of Inflammation)
Recent studies from the Gulf region suggest that compared to men, women have a greater risk of developing metabolic syndrome (MeS). Objective. To investigate gender differences in body composition, adipokines, inflammatory markers, and aerobic fitness in a cohort of healthy Qatari adults. Participants. Healthy Qatari (n=58) were matched for age, gender, and body mass index. Methods. Body composition and regional fat distribution were determined by dual-energy X-ray absorptiometry and computerized tomography. Laboratory assessments included serum levels of fasting glucose, insulin, lipid profile analysis, adipokines, and inflammatory markers. Subjects were also evaluated for aerobic fitness. Results. Women had more adipose tissue in the total abdominal (P=0.04) and abdominal subcutaneous (P=0.07) regions compared to men. Waist circumference and indices of insulin sensitivity were similar; however, women had a more favourable lipid profile than men. Serum adiponectin and leptin levels were significantly higher in women, whereas inflammatory profiles were not different between men and women. Aerobic fitness was lower in women and was associated with abdominal fat accumulation. Conclusion. In premenopausal women, higher levels of adiponectin may support maintenance of insulin sensitivity and normolipidemia despite greater adiposity. However, poor aerobic fitness combined with abdominal fat accumulation may explain their greater future risk of MeS compared with men.